Education, Community Participation, and Satisfaction: An Overview of Pakui Sayang Park as an Open Sports Space - Usman, Arifuddin; Rusli, Dewi Hapipa; Hudain, Muh. Adnan; Saharullah, Saharullah; Sahabuddin, Sahabuddin (Education and Talent Development Center Indonesia (ETDC Indonesia), 2024)
The study aimed to (1) assess the community's involvement in the availability of Pakui Sayang Park as a sports open space in Makassar and (2) gauge the public's satisfaction with the park's status as a sports open space in Makassar. The samples in this study were students, the community, and employees in Pakui Sayang Park. employees at Pakui Sayang Park Makassar City totaling 30 people, sampling techniques. people, sampling method using purposive sampling. We conducted this survey-based research, employing a descriptive design and a percentage-based data analysis, using the SPSS Version 26.0 program and Microsoft Excel 2019. The results of this study indicate that: (1) community participation in the availability of pakui sayang park as a sports open space in Makassar is in the excellent category at the level of 70%, and (2) community satisfaction with the availability of pakui sayang park as a sports open space in Makassar is in a good category or 83%. This study also identified four primary areas of satisfaction: quality and service, price, emotional factors, and convenience. However, further research is necessary. However, we must conduct additional research to understand the factors influencing community participation and satisfaction with physical activity in Pakui Sayang Park.